2013
DOI: 10.4085/1062-6050-48.4.02
|View full text |Cite
|
Sign up to set email alerts
|

National Athletic Trainers' Association Position Statement: Conservative Management and Prevention of Ankle Sprains in Athletes

Abstract: Objective: To present recommendations for athletic trainers and other allied health care professionals in the conservative management and prevention of ankle sprains in athletes.Background: Because ankle sprains are a common and often disabling injury in athletes, athletic trainers and other sports health care professionals must be able to implement the most current and evidence-supported treatment strategies to ensure safe and rapid return to play. Equally important is initiating preventive measures to mitiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
233
0
15

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(261 citation statements)
references
References 163 publications
1
233
0
15
Order By: Relevance
“…An expert panel assembled by the National Athletic Trainers Association published a position paper on guidelines for the evaluation and treatment of the ankle sprain in athletes. 17 For podiatric physician this resource is an excellent comprehensive review of current evidence-based recommendations for the evaluation and treatment of the ankle sprain.…”
Section: Evaluation and Treatmentmentioning
confidence: 99%
“…An expert panel assembled by the National Athletic Trainers Association published a position paper on guidelines for the evaluation and treatment of the ankle sprain in athletes. 17 For podiatric physician this resource is an excellent comprehensive review of current evidence-based recommendations for the evaluation and treatment of the ankle sprain.…”
Section: Evaluation and Treatmentmentioning
confidence: 99%
“…It is reported that 77-83% of all ankle sprains are focal to the lateral ligament complex (Hawkins et al, 2001;Price et al, 2004;Woods et al, 2003), with excessive loading during inversion and plantar flexion the most common mechanism of injury (Ferran & Maffulli, 2006;Kaminski et al, 2013). When the foot is forced into a compromised position, the mechanoreceptors in the ankle ligaments and joint capsule sense the extreme or sudden movements and initiate a dynamic restraint (Hertel, 2002;Konradsen et al, 1997;Hertel, 2000;Jackson et al, 2009;Michelson & Hutchins, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Both range of motion (ROM) and strength defi cits have been established in players who suffered an ankle injury [ 8 ]. Although no research is available on the effectiveness of strength training programmes to reduce the risk of ankle injury, these defi cits suggest that strength and fl exibility training may have a preventive effect.…”
Section: Strength Trainingmentioning
confidence: 99%
“…Repetition of such testing at regular intervals may chart a player's progress after exercises are prescribed. Although there is no consensus on the exact training mode and intensity for optimal recovery, it is recommended that both open and closed chain exercise in a variety of modes should be performed [ 8 ]. For range of motion, especially ankle dorsifl exion should be targeted.…”
Section: Strength Trainingmentioning
confidence: 99%